Evaluation of Optimum Temperature and Soaking Time for Reduction of Nitrite Levels in Cirebon Typical Salted Fish - M. Duddy Satrianugraha; Risnandya Primanagara; Amanah (Fakultas Kedokteran UGJ Cirebon, 2024)
biolibium@gmail.com Abstract. Salted fish is one of Indonesia most common side dish. Processing salted fish into ready-to-eat usually done by immersing salted fish in the water. Else of reducing the saltines and soaking can also reduce harmful compounds like nitrite, which can disrupt the blood's oxygen-binding process. Nitrite can build up methemoglobin compounds which disrupt oxygen supply. The study aims to determine which temperature and length of time to soak salted fish effectively reduce nitrite levels. This experimental laboratory study uses a Pre-Posttest Control Group Design. The samples chosen were jambal roti, peda and gubaran salted fish. Five grams of the sample were immersed in a temperature of 400C, 500C, 600C, 700C with immersion time of 10, 15, 20, 25 minutes respectively with a completely randomized design (CRD). The immersion was repeated three times, and the average nitrite levels in the water were compared between temperature, immersion time, and type of fish. Statistically, the most effective temperature to reduce nitrite is 700C with a soaking time of 20 minutes. The fish's size influences the effectiveness, wherein gubaran salted fish is a thin sheet so that it has more surface area. In conclusion, the most effective soaking time is 20 minutes at 700C